The Influence of Entrepreneurship Practices and Digital Literacy on Entrepreneurial Motivation in Semester VIII Students at Bhinneka PGRI University,Tulungagung - Rafi, Mohamad; Rindrayani, Sulastri Rini (9 772338317006, 2024)
The Influence of Entrepreneurship Practices and Digital Literacy on Entrepreneurial Motivation in Semester VIII Students at Bhinneka PGRI University,Tulungagung.With problems related to human resources, economic growth will be difficult to achieve easily. One of the problems associated with human resources is unemployment. The increase in unemployment that occurs today is due to the lack of availability of jobs for the community, especially graduates of the educated group. This condition indicates that unemployment is a serious problem that must be addressed immediately. To reduce unemployment, higher education as the highest level of formal education must be able to educate an independent and capable young generation by inspiring or motivating students to create jobs by becoming an entrepreneur with the existence of entrepreneurship practice education being one of the good bridges to encourage students to dare to be entrepreneurs because in entrepreneurship practice students can learn firsthand about all conditions for building or developing a business in the future supported by digital sophistication students must be able to take advantage of digital literacy used to access entrepreneurship and maximize their business in the current era and in the era to come. Therefore, this study aims to determine the effect of entrepreneurial practice and digital literacy on entrepreneurial motivation in 8th semester students of Bhinneka PGRI University Tulungagung.Keywords: Entrepreneurial Motivation, Entrepreneurship Practices, Digital Literacy.